Fiscal Management of Scaled-Up Aid - Gupta, Sanjeev; Adenauer, Isabell; Fletcher, Kevin; Last, Duncan (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses the role of fiscal policy and fiscal institutions in managing scaled-up aid. In an environment of volatile scaled-up aid, fiscal policy formulation should be anchored in medium-term frameworks, incorporating a longer-term view of potential resource availability and spending plans. There is merit in smoothing expenditures over time so that all programs are adequately funded. The paper argues that wage-bill ceilings should be used in Fund-supported programs only in exceptional cases. The paper also discusses basic reforms for strengthening public financial management systems for effective utilization of scaled-up aid flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet